Corporate reporting of intellectual capital: evidence from ace market of bursa Malaysia / Ruhaya Atan, Azlina Rahim and Saunah Zainon - Atan, Ruhaya; Rahim, Azlina; Zainon, Saunah (2011)
This study investigates the corporate reporting practice of intellectual capital in MESDAQ market Bursa Malaysia. It also identify the factors that influences the reporting of intellectual capital in MESDAQ’s annual reports. Data will be collected from the annual reports of the selected companies for year 2009. The extent of ICD is measured by intellectual capital framework and content analysis is performed on the companies’ annual reports. In order to determine the factors that influences the ICD, this research assess the association of firm’s characteristics; firm size, type of industry, type of auditor, profitability and IC disclosure. The relationship between firm’s characteristics and ICD can be evaluated by developing research hypotheses. Empirical test will be conducted on 105 companies listed under MESDAQ Market. Since there is no accounting standard on ICD, this study may provide useful inputs to the policymakers for future accounting guideline.